Acute inflammatory response following lower-and upper-body Wingate anaerobic test in elite gymnasts in relation to iron status - Kochanowicz, Andrzej; Waldziński, Tomasz; Niespodziński, Bartłomiej; Brzezińska, Paulina; Kochanowicz, Magdalena; Antosiewicz, Jedrzej; Mieszkowski, Jan (Frontiers in Physiology, 2024)
Artistic gymnastics is one of the most demanding sports disciplines, with the athletes demonstrating extremely high levels of explosive power and strength. Currently, knowledge of the effect of gymnastic training adaptation on exercise-induced inflammatory response is limited. The aim of the study wasstudy aimed to evaluate inflammatory response following lower-and upper-body high-intensity exercise in relation to the iron status in gymnasts and non-athletes. Fourteen elite male artistic gymnasts (EAG, 20.6 ± 3.3 years old) and 14 physically active men (PAM, 19.9 ± 1.0 years old) participated in the study. Venous blood samples were taken before, and 5 min and 60 min after two variants of Wingate anaerobic test (WAnT), upper-body and lower-body WAnT. Basal iron metabolism (serum iron and ferritin) and acute responses of selected inflammatory response markers [interleukin (IL) 6, IL-10, and tumour necrosis factor α] were analyzedanalysed. EAG performed significantly better during upper-body WAnT than PAM in terms of thein terms ofregarding relative mean power and peak power. The increase in IL-6 levels after upper-body WAnT was higher in EAG than that in PAM; the opposite was observed after lower-body WAnT. IL-10 levels were higher in EAG than those in PAM, and tumour necrosis factor α levels were higher in PAM than those in EAG only after lower-body WAnT. The changes in IL-10 correlated with baseline serum iron and ferritin in PAM. Overall, gymnastic training is associated with the attenuation of iron iron-dependent post-exercise anti-inflammatory cytokine secretion.